Design of Self-Powered Solid-State Fault Current Limiters for VSC DC Grids - Xu, Jun; Gao, Lei; Zhang, Huiyuan (Frontiers in Energy Research, 2021)
Fault current limiters (FCLs) can suppress the rising of short-circuit fault currents in voltage source converter (VSC) based DC grids. However, the power electronic switches of FCLs need extra source equipment to supply power, which increases the complexity and cost. This paper presents three kinds of self-powered solid-state FCLs (SSFCLs). The proposed self-powered SSFCLs can detect short-circuit faults by sensing fault current increasing and draw energy from the fault DC line to drive the power electronic switches automatically. The self-powered SSFCLs are equipped with a self-powered supply system (SPSS). The SPSS can obtain energy from the magnetic field induced by short-circuit fault current using magnetic-coupling mutual inductance coils. In PSCAD/EMTDC, the proposed self-powered SSFCLs are placed directly on the DC line without external power supply equipment. When a short-circuit fault occurs, the simulation results verify that the proposed self-powered SSFCLs can rapidly acquire power to drive the power electronic switches and then suppress the rise of fault current. The proposed self-powered SSFCL prototypes provide a solution for decreasing the cost and complexity associated with installing extra source equipment.